2023
DOI: 10.3390/foods12071354
|View full text |Cite
|
Sign up to set email alerts
|

Study on Hyperspectral Monitoring Model of Total Flavonoids and Total Phenols in Tartary Buckwheat Grains

Abstract: Tartary buckwheat is a common functional food. Its grains are rich in flavonoids and phenols. The rapid measurement of flavonoids and phenols in buckwheat grains is of great significance in promoting the development of the buckwheat industry. This study, based on multiple scattering correction (MSC), standardized normal variate (SNV), reciprocal logarithm (Lg), first-order derivative (FD), second-order derivative (SD), and fractional-order derivative (FOD) preprocessing spectra, constructed hyperspectral monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The colonization of Tartary buckwheat by S. indica significantly increased the soluble sugar content in the leaves of Tartary buckwheat (p < 0.01); the soluble protein content also increased (p < 0.05). At the same time, due to the rich content of flavonoids (Figure 6D) and phenolic (Figure 6C) substances in Tartary buckwheat [38], we also measured the total flavonoids and total phenols content of the leaves and seeds of S. indica-colonized and non-colonized Tartary buckwheat. The results showed that the total flavonoid and total phenolic contents in the leaves and seeds of Tartary buckwheat extremely significantly increased after colonization by S. indica (p < 0.001).…”
Section: Effects Of S Indica On Metabolites Of Tartary Buckwheatmentioning
confidence: 99%
“…The colonization of Tartary buckwheat by S. indica significantly increased the soluble sugar content in the leaves of Tartary buckwheat (p < 0.01); the soluble protein content also increased (p < 0.05). At the same time, due to the rich content of flavonoids (Figure 6D) and phenolic (Figure 6C) substances in Tartary buckwheat [38], we also measured the total flavonoids and total phenols content of the leaves and seeds of S. indica-colonized and non-colonized Tartary buckwheat. The results showed that the total flavonoid and total phenolic contents in the leaves and seeds of Tartary buckwheat extremely significantly increased after colonization by S. indica (p < 0.001).…”
Section: Effects Of S Indica On Metabolites Of Tartary Buckwheatmentioning
confidence: 99%